If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 0 + -1(-2) Multiply -1 * -2 2y = 0 + 2 Combine like terms: 0 + 2 = 2 2y = 2 Solving 2y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 1 Simplifying y = 1
| -1y=0x+10 | | 87-x=135 | | 6(2x)-48=0 | | 2n+6=n+8 | | 2y=0-6 | | x^3+1/8 | | (4x+3)(3y-8)= | | 0x-2y=6 | | 356+56x=-832 | | 2s^2=50 | | -5(x+2)+9=-1 | | x^2-4y^2+4x+8y-16=0 | | 15x+14=2(5y+6) | | 4x+6x=180 | | 2x-4+x=11 | | 3/4x-(8)=25 | | Tn=4n-11 | | -12+x+2x=9 | | 24.6+3.69/4=9.54 | | 4y-6y+9=-2 | | 6+7x=4+2x | | 8+6a=-29+24 | | (3/7/7/3)*5/9 | | -2+3x-x=12 | | -2.3q+16=2.2x-4.5 | | 3/7/7/3*5/9 | | m^2+20m=0 | | D/310=7 | | -2+3x-x=4 | | -9q-17=10 | | 5y=0x+15 | | 5x+10=4x+20 |